The Academic, Societal and Animal Welfare Benefits of Open Science for Animal Science - Nawroth, Christian; Krause, E. Tobias (Frontiers in Veterinary Science, 2022)
The benefits of Open Science (OS) for academic and societal issues are relatively generalizable across scientific disciplines. OS practices here have the potential to increase public trust in research findings due to heightened transparency. In addition, animal science, as all research involving experiments with animals, has the obligation to reduce, refine, and replace the usage of animals in research, the so-called 3R-principles. An efficient adherence to these principles would be improved by transparently publishing research findings, data and protocols. This can be accomplished via the means of a variety of OS practices. OS should thus be considered by animal science researchers as a valuable opportunity that can contribute to the adherence to these 3R-principles. We stress the need for future investigations on the crossroads of OS and the specific issues that experiments in the field of animal science often face, such as frequent adaptation of novel test protocols. We also want to encourage animal science researchers to implement a diverse set of OS practices in their workflows, a notion that could be, next to other measures, implemented by providing workshops and courses in research training for Early Career Researchers, but also for senior PIs. We acknowledge that implementing OS practices can be accompanied with specific downsides, such a potentially initally increased time investment and an initial lack of conformity by peers on this issue. Nevertheless, engaging in these practices will move the field forward compared to the current situation of not being (fully) open and transparent about animal research.